2016
DOI: 10.1016/j.fertnstert.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of the tachykinins substance P/neurokinin A/hemokinin-1 and their preferred neurokinin 1/neurokinin 2 receptors in uterine leiomyomata

Abstract: These and our previous data demonstrate that the whole tachykinin system is differentially regulated in leiomyomas. The increased expression of NK1R-Tr might stimulate leiomyoma growth in a similar way to that observed in other steroid-dependent tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Further studies need to be conducted with a larger sample size focusing on longitudinal changes and any differences between various tendinopathy sites. Next, it is debatable that TAC1 gene expression was considered as representative of SP expression in our study, given that TAC1 not only codes for SP , but also encodes neurokinin A [50]. This was supported by the fact that SP is well known as the major neuropeptide synthesized from the TAC1 gene and found several studies that regarded TAC1 as representative of SP expression [51,52].…”
Section: Discussionmentioning
confidence: 82%
“…Further studies need to be conducted with a larger sample size focusing on longitudinal changes and any differences between various tendinopathy sites. Next, it is debatable that TAC1 gene expression was considered as representative of SP expression in our study, given that TAC1 not only codes for SP , but also encodes neurokinin A [50]. This was supported by the fact that SP is well known as the major neuropeptide synthesized from the TAC1 gene and found several studies that regarded TAC1 as representative of SP expression [51,52].…”
Section: Discussionmentioning
confidence: 82%
“…NK1R is expressed in human and rodent uterus 6669 , so are CRLR and RAMP1 70 . The expression of NK1R and SP-coding gene TAC1 is reported to be upregulated by estrogen 68,71 and TNF-α 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Neuropeptide signaling through the receptors is well known to regulate various physiological functions such as induction of pain response, relaxation of smooth muscle, dilation of blood vessels, and vascular permeability. It has been demonstrated that tachykinins and their receptors are expressed in several non‐neuronal cells, which connect the nervous and peripheral organ systems to control respiratory, cardiovascular, endocrine, and gastrointestinal activity 2,4 . Furthermore, recent studies revealed that neuropeptide receptors are expressed in various cancer cells in the tumor microenvironment, therefore tachykinin signaling through these receptors possibly regulates pathological functions related to the development of cancer and tumor malignancy 5,6 …”
Section: Introductionmentioning
confidence: 99%